GAMBARAN PENGETAHUAN PERAWAT TENTANG CODE BLUE PASIEN CARDIAC ARREST - Ririn Heryati; Dayat Trihadi; Dwi Yogo Budi Prabowo (STIKES Telogorejo Semarang, 2024)
Cardiac arrest is a critical emergency that requires prompt intervention. Nurses play a crucial role in activating the code blue system, which necessitates a thorough understanding of the procedures involved. Adequate knowledge among nurses is essential for effective management of cardiac arrest cases and achieving the goals of the code blue system. This study aims to assess the level of knowledge among nurses about the code blue protocol for cardiac arrest patients. This quantitative research employed a descriptive study design. The sample consisted of 33 nurses working in the Bougainville Ward at SMC Telogorejo Hospital. Knowledge levels were evaluated using a structured questionnaire. The study revealed that the majority of nurses in the Bougainville Ward had a good understanding of the code blue procedures, with 26 respondents (78.8%) demonstrating a high level of knowledge. The findings indicate that a significant proportion of nurses possess a good level of knowledge regarding code blue protocols for cardiac arrest. To maintain and enhance this knowledge, it is recommended that hospitals continue to provide training opportunities. Further research could explore the correlation between nurses’ characteristics and their knowledge of code blue procedures.